Consensual Contract to Transfer Vehicle Ownership in Iraqi Law - Amez Fatih Mohamedsaleh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The consensual contract to transfer vehicle ownership is a widespread subject in Iraq and the Kurdistan region, and creates many legal problems in its legal adaptation and in its effects that depend on this adaptation. These problems are apparent in the jurisprudence’s handling of the subject, and these problems are also reflected in the decisions of the judiciary in Iraq and the Kurdistan region, which includes more than one trend in this regard. This study is an attempt to explore the subject of the consensual contract to transfer vehicle ownership in Iraqi law in both jurisprudence and the judiciary in order to realize its concept, characteristics, legal adaptation and effects. Accordingly, the study was divided into two sections. In the first one, we defined the consensual contract to transfer vehicle ownership through clarifying its concept and characteristics, and in the second section we explored the legal adaptation of this contract and its effects. In the conclusion of the study, we presented the results that we reached in the folds of the study and the suggestions that we presented regarding the subject of the study. One of the results of this study is that the consensual contract to transfer vehicle ownership in Iraqi law is an indefinite contract, which arises from the beginning in this way, and without being the result of the transformation from a void contract. It is a distinct contract in its origin and effects from the contract that conveys vehicle ownership. The study also presented several suggestions with texts, in the hope that they could be used from the Iraqi legislature, to evaluate the legislative regulation of the consensual contract to transfer vehicle ownership, and to end the confusion and ambiguity regarding its legal adaptation and its effects.